Perancangan Sentra Budidaya Ikan Air Tawar di Provinsi Gorontalo dengan Pendekatan Arsitektur Ekologi - Rahmat Saidi; Muh. Rizal Mahanggi; Satar Saman (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
Gorontalo Province has abundant freshwater resources, yet lacks integrated and sustainable aquaculture facilities. This article presents the conceptual design of a Freshwater Fish Aquaculture Center in Gorontalo Province as a response to this condition, applying Ecological Architecture as the primary design approach. The designed area accommodates various activities including freshwater fish cultivation, education, tourism, as well as research and development of fisheries technology. The method used is a qualitative descriptive approach through literature studies, field observations, interviews, and precedent studies. The design results show that the area can be divided into four main zones: the aquaculture zone, education zone, tourism zone, and supporting zone. The ecological approach is realized through the use of natural lighting and ventilation, environmentally friendly materials, an integrated water management system, and the maximization of green open spaces. This design is expected to increase fisheries productivity while promoting community empowerment through educational activities and environmentally sustainable tourism.